Real-Time Elastography versus Shear Wave Elastography on Evaluating the Timely Radiofrequency Ablation Effect of Rabbit Liver: A Preliminary Experimental Study - Li Shi; Xiaoju Li; Wei Liao; Wenxin Wu; Ming Xu (Diagnostics, 2023)
Purpose: to evaluate and monitor the timely thermal ablation changes of rabbit liver by using two elastographic methods—real-time elastography (RTE) and shear wave elastography (SWE)—as compared to contrast-enhanced ultrasound (CEUS) and physical specimens. Materials and Methods: 20 ablation zones were created in the livers of 20 rabbits using radiofrequency ablation (RFA). After the ablation, RTE and SWE were used to measure the elastic properties of the twenty ablation zones. The consistency of efficacy evaluation for RTE and SWE measurements was analyzed using the Bland–Altman test. The areas of the thermal ablation zones were also measured and compared according to the images provided by RTE, SWE, CEUS, and gross physical specimen measurement. Results: RTE and SWE could clearly display the shape of RFA ablation zones within one hour after the ablation. The average elasticity ratio for the ablation zone measured by RTE was 3.41 ± 0.67 (2.23–4.76); the average elasticity value measured by SWE was 50.7 ± 11.3 kPa (33.2–70.4 kPa). The mean areas of the ablation zones measured with RTE, SWE, gross specimen, and CEUS were 1.089 ± 0.199 cm2, 1.059 ± 0.201 cm2, 1.081 ± 0.201 cm2, and 3.091 ± 0.591 cm2, respectively. The Bland–Altman test showed that RTE and SWE have great consistency. Area measurements by CEUS were significantly larger than those of the other three methods (p < 0.05). Conclusion: RTE and SWE are both able to accurately confirm the range of ablation zones shortly after the ablation for rabbit livers.